2012
DOI: 10.1097/ta.0b013e318265fc04
|View full text |Cite
|
Sign up to set email alerts
|

Using trauma center data to identify missed bicycle injuries and their associated costs

Abstract: Epidemiologic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Trends in bicycle-related injuries are difficult to assess because the majority of nonfatal injuries sustained while cycling are not reported to police and thus are not included in traffic statistics. 1 We sought to evaluate trends in adult cycling injuries and hospital admissions in the United States using emergency department data.…”
mentioning
confidence: 99%
“…Trends in bicycle-related injuries are difficult to assess because the majority of nonfatal injuries sustained while cycling are not reported to police and thus are not included in traffic statistics. 1 We sought to evaluate trends in adult cycling injuries and hospital admissions in the United States using emergency department data.…”
mentioning
confidence: 99%
“…We believe that the number of head trauma cases with fatal outcomes can be reduced by generalizing helmet use. A study from United States of America reported that the total cost of 2054 patients presenting to hospitals after bicycle accidents was 30.4 million Dollars [11]. Another study found that the cost of injuries to drink bicycle riders was higher than that of injuries to non-drink bicycle riders [12].…”
Section: Discussionmentioning
confidence: 99%
“…ZSFG is San Francisco’s only Level I trauma center for the city of San Francisco and Northern San Mateo county. All trauma patients who are admitted to ZSFG are entered into a prospective, longitudinal trauma disease registry [5]. We performed a retrospective chart review of cases that involved a bicycle injury.…”
Section: Methodsmentioning
confidence: 99%
“…Nationally, 1% of the country utilizes a bicycle to commute to work [4]. Within San Francisco, over 3% of inhabitants cycle daily [5]. This is in part due to improvements in cycling infrastructure and community support.…”
Section: Introductionmentioning
confidence: 99%